Toxicological and Immunological Effects oÂ·f th.e Insecticide Diazinon in Male Albino Mice - AI-R.ubae, A. Y.; Mohammed, B. M.; Al- shanli, F .H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This st4dy  has been ccil'ndÂ·uctedÂ· to Â·shed a1ight 00: thetox:icologital Â®d irmm.J,nological effects.of the insectiCide Diaziuonon male albino mice.In order to determine the dose   whiCh should be ut\lized in hechrqn:ic exposure  study, the LD:so valubas established  which rea.ched58 mg l kg  of b0dy weight . Various parameters wereÂ· utHizea in• evaluatitig'the effects of tb:e.Â·ins.ecticide in fo.ut Weeks ami ig}1t weeks..p,ost  ora.l - e.xposure l'lsing the concentrations 5, lb-  l.5 Â· mg I kg  body• W.eight. Resu}Js sh Jwed an.Â·in.e:Eeasc in the ni.r!J!ber ofplague.s , which was not statistically sigpific(l_nt a,fte.r twenty eight dayof ex.p(rs:ure to the insecticide at the concentration 5 ppm.The passive ha:emaglutinationÂ· sh.owed a .Significant decrease Â· intibÂ·ody titer at (   p oo  I  ) post exposure peri0ds. (28,56  d) utilhingthe tlfree variops conc ntrati'ons.ResuJ.tsÂ·of Arthus ttist indicjlte.d a decline in  j.ts valu(} but 'it was riot statiSti